2016
DOI: 10.1016/j.trim.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immune activation on the risk of allograft rejection in human immunodeficiency virus-infected kidney transplant recipients

Abstract: Background HIV infection is associated with high rates of acute rejection following kidney transplantation. The underlying mechanisms for such predisposition are incompletely understood. Pathological immune activation is a hallmark of chronic HIV infection that persists despite effective antiretroviral therapy. We hypothesized that the baseline levels of T cell activation in HIV+ candidates would correlate with their risk of acute rejection following kidney transplantation. Methods Single-center retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Consistent with previous studies of kidney transplantation in HIV 1 5 , we observed excellent transplant outcomes without evidence of HIV disease progression. The most important finding of the present study is the association between PI use and adverse outcomes, namely reduced three-year patient and graft survival, and increased risk of serious non-opportunistic infections.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous studies of kidney transplantation in HIV 1 5 , we observed excellent transplant outcomes without evidence of HIV disease progression. The most important finding of the present study is the association between PI use and adverse outcomes, namely reduced three-year patient and graft survival, and increased risk of serious non-opportunistic infections.…”
Section: Discussionsupporting
confidence: 91%
“…CNI levels at 4, 12, 26 and 52 weeks were comparable across ART groups. Other factors, such as infection of the allograft, previous alloimmunization and immune activation, might also play a role in predisposition to rejection 3 , 5 , 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintenance IS included tacrolimus, mycophenolate mofetil, and prednisone. Additional details about IS and antimicrobial prophylaxis protocols at our center have been previously described …”
Section: Methodsmentioning
confidence: 99%